Bioactive Ag3PO4/Polypropylene Composites for Inactivation of SARS-CoV-2 and Other Important Public Health Pathogens - Ribeiro, Lara K.; Assis, Marcelo; Lima, Lais R.; Coelho, Dyovani; Gonçalves, Mariana O.; Paiva, Robert S.; Moraes, Leonardo N. [UNESP]; Almeida, Lauana F. [UNESP]; Lipsky, Felipe; San-Miguel, Miguel A.; Mascaro, Lúcia H.; Grotto, Rejane M. T. [UNESP]; et al. (American Chemical Society (ACS), 2021)
The current unprecedented coronavirus pandemic (COVID-19) is increasingly demanding advanced materials and new technologies to protect us and inactivate SARS-CoV-2. In this research work, we report the manufacture of Ag3PO4 (AP)/polypropylene (PP) composites using a simple method and also reveal their long-term anti-SARS-CoV-2 activity. This composite shows superior antibacterial (against Staphylococcus aureus and Escherichia coli) and antifungal activity (against Candida albicans), thus having potential for a variety of technological applications. The as-manufactured materials were characterized by XRD, Raman spectroscopy, FTIR spectroscopy, AFM, UV-vis spectroscopy, rheology, SEM, and contact angle to confirm their structural integrity. Based on the results of first-principles calculations at the density functional level, a plausible reaction mechanism for the initial events associated with the generation of both hydroxyl radical •OH and superoxide radical anion •O2- in the most reactive (110) surface of AP was proposed. AP/PP composites proved to be an attractive avenue to provide human beings with a broad spectrum of biocide activity.